2017
DOI: 10.1590/s0102-053620170216
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical attributes of no-till Brassica crops cultivated after various cover crops

Abstract: Cauliflower and cabbage require high amounts of nutrients in short periods of time; however, the intensive use of inorganic fertilizers can cause nutritional imbalances in these crops and reduce the quality of the final product. This study evaluated the chemical composition and yield of no-till cauliflower and cabbage grown on residues of various cover crops in Uberaba, Minas Gerais State, Brazil. The experimental design was randomized blocks with four cover crops (sunn hemp, brachiaria, pearl millet and fallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Pinho et al (2003) studied the physical and chemical parameters of specialty corn cultivars and obtained AA content of 9.6 to 11.5 mg 100 g -1 . Torres et al (2017) also reported a rise in AA levels when cauliflower and cabbage were grown on brachiaria residue.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Pinho et al (2003) studied the physical and chemical parameters of specialty corn cultivars and obtained AA content of 9.6 to 11.5 mg 100 g -1 . Torres et al (2017) also reported a rise in AA levels when cauliflower and cabbage were grown on brachiaria residue.…”
Section: Resultsmentioning
confidence: 90%
“…According to Franco (2005), the chemical composition and energy content for every 100 g fresh sweet corn are 386.5 calories, 66.7 g of glycine, 11.62 g of PTN, and 8.1 g of LIP, lower than the PTN and LIP values recorded in the present study. Torres et al (2017) studied the chemical quality of brassica crops grown in the Cerrado on different cover crop residues and found higher PTN values for cauliflower cultivated with sunn hemp residue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In organic farming systems, because of restrictions on the use of chemicals, mulching can be quite advantageous as a means of weed control (Resende et al, 2005). However, the type of mulch in use can influence weed management (Queiroga et al, 2002;Campiglia et al, 2010;Sediyama et al, 2010) and crop yield (Torres et al, 2017). Brachiaria has been noted for its easy establishment and considerable biomass production during the year, which results in excellent mulch (Timossi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%